Review Of Smart Environment Tourism Indicator Policies In The Development Of The Likupang Tourism Special Economic Zone - Felly Ferol Warouw; Viktory Nicodemus Joufree Rotty; Piet Hein Pusung; Lady Grace Jane Giroth (Universitas Padjadjaran, 2023)
This research is to analyze the application of tourism smart environment policies in the development of the Likupang Tourism Special Economic Zone (SEZ) in North Sulawesi, Indonesia. The data publication policy is explained by using a qualitative approach method. Assessment based on scores based on tourism smart environment indicators. The results of the study show that the tourism potential in the Likupang area is the government's policy by proposing this area as a tourism special economic zone. The policy was published in the form of Government Regulation number 84 of 2019 as a Legal Basis with an area of 197.4. The first question which describes the findings of the literature carried out in journal articles shows that the vision of a smart environment tourism policy in the development of the Likupang Tourism Special Economic Zone in the era of the COVID-19 pandemic has been carried out a lot. The second question is the researcher's attempts to trace the perception of stakeholders to the understanding of stakeholders about whether or not it is necessary to develop a smart environment in the Likupang SEZ area using a smart environment tourism approach at an ecocentrism or supportive level. The third question can be seen from the process of implementing the Likupang SEZ which is the government's effort to develop regional tourism potential, of course with a smart environment tourism approach as well as a way to reduce emissions, manage waste and involve community participation.